2017
DOI: 10.1371/journal.pone.0184809
|View full text |Cite
|
Sign up to set email alerts
|

Quality control processes in allografting: A twenty-year retrospective review of a hospital-based bone bank in Taiwan

Abstract: Musculoskeletal allografts are now commonly used. To decrease the potential risks of transmission of pathogenic bacteria, fungi, or viruses to the transplant recipients, certain issues regarding the management of patients who receive contaminated allografts need to be addressed. We aimed to clarify the incidence and extent of disease transmission from allografts by analyzing the allografting procedures performed in the bone bank of our hospital over the past 20 years. We retrospectively reviewed the data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Surgical site infection (SSI) as a repercussion of the contaminated bone allograft is uncommon and ranges between 1.3% and 12%. 1,8,9 The overall allograft-related infection rate after 13 years of bone banking was 1.80%. The organism most commonly identified was the Staphylococcus spp in both audits.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical site infection (SSI) as a repercussion of the contaminated bone allograft is uncommon and ranges between 1.3% and 12%. 1,8,9 The overall allograft-related infection rate after 13 years of bone banking was 1.80%. The organism most commonly identified was the Staphylococcus spp in both audits.…”
Section: Discussionmentioning
confidence: 99%
“…Allografts are frequently used in orthopedic reconstructive procedures, and successful outcomes after allograft implantation depend on the quality control of bone bank processing. The bone bank can store allografts from living or cadaveric donors and safely supply them for recipients, and must prevent the transmission of infectious diseases and malignancies through routine culture swabs and serological screening [ 2 , 4 , 5 , 7 ]. However, there are no uniform guidelines for the management of bone banks, and most bone bank protocols for quality control follow the guidelines recommended by the American Association of Tissue Banks and also meet the national law standards [ 1 , 3 , 6 , 14 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall positive bacterial culture rate of after-thawing allografts before implantation ranged from 1% to 12%, and the infection rate in recipients with contaminated allograft was reported as being from 0% to 10% [ 1 , 2 , 5 , 6 , 11 , 12 , 13 ]. However, the infective pathogens of postoperative surgical site infections were different from the cultured microorganisms of thawed allografts [ 1 , 2 , 5 , 6 , 11 , 12 , 13 ]. Sims et al reported that 43 implanted allografts (43/996, 4.3%) had positive bacterial growth, and significant postoperative infection developed in two patients (4.6%) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disadvantages of allograft include reducing osteogenicity and osteoconductivity due to processing and the risk of disease transmission 3 , 9 . For the best outcomes, bone allografts from organ donors should include a strict allograft process (namely, well-controlled harvesting, packaging, and storage in a bone bank) and optimal size-matching between the donor and host at the time of surgery 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%